Remesas fantasmas y familias divididas del norte y centro de México - Genoveva Flores Quintero (Les Cahiers ALHIM)
This article analyzes the particular effect of the new Mexican law over the exchange of dollars published in the Diario Oficial last July, in the zone in the frontier between Mexico and the United States, where 20 millions of Mexicans live. In this territory a new system of remittance exchange has been developed in the last years. In the base of that system lies the migrant’s salary which is the second most important money coming source after the petroleum incomes for Mexico; these migrant incomes support the rural economy of little towns close the frontier and cities in the center of Mexico, but they have become dollar dependents in the economic sense. In normal conditions migrants send money from U.S.A. to Mexico by money orders or electronic transferences, but these services are expensive for the migrants and because of that, they turn to send the cash by people that cross legally the frontier towards Mexico. That economical dynamic is being interrupted by the new Mexican law and the economy that depends on it is being broken. In addition the migrants and their families live in a violence environment as a result of drug trafficking war.